Effect Of Different Pre-Treatments On Functional And Physicochemical Properties Of Octenyl Succinic Anhydride (Osa) Modified Sago Starch In Pickering Emulsion - Rozman, Norrazatin Haida (University Science Malaysia, 2019)
Particle-stabilized emulsions, called Pickering emulsions, can be produced by using starch particles. This work aims to understand how the properties of the starch particles affect the droplet size and creaming of such emulsions. In the study, sago starch (Metroxylon spp.) particles were pre-treated by two different methods and used to stabilize Pickering emulsion (mayonnaise). High power ultrasonication and acid hydrolysis pre-treatments were used to obtain smaller particles. All samples were modified with octenyl succinic anhydride (OSA) to increase their hydrophobicity with a level of OSA substitution of 3%. Degree of substitution (DS) was the highest (0.0206) for AOS and 0.0123 for HOS. In comparison to native starch, FTIR spectroscopy showed that pre-treated OSA sago starch had two additional bands at 1725 cm-1 and 1570 cm-1. The morphology of sago starch granule examined using scanning electron microscopy (SEM) showed some rough surface, cavitation and erosion on OSA sago starch. The emulsification index (EI) increased for the pre-treated OSA sago starch owing to the size reduction of starch particles. Mayonnaise with 75% and 100% pre-treated OSA sago starch kept their emulsion stabilize after 21 days while mayonnaise formulated with OSA sago starch exhibited creaming. The emulsifying activity (EA) of mayonnaise stabilized with pre-treated OSA sago starch showed smaller droplet size with significantly difference (p< 0.05) with respect to structural disorder that occurs during pre-treatments and modifications.